Factors affecting the distribution of the sibling species of treecreepers Certhia familiaris and C. brachydactyla in the Pyrenees - Clouet, Michel; Gerard, Jean-François (Journal of ornithology, 2019)
We investigated the main environmental variables determining the occurrence of the Eurasian Treecreeper Certhia familiaris and Short-toed Treecreeper C. brachydactyla within the mountain range of the Pyrenees. Presence/absence data were obtained, using the response to the playback of each species’ typical song; they were collected during the springs of 2004–2012 over 487 sites, within 33 areas of mature forest distributed over the mountain range. The analysis, based upon generalised linear models, showed that altitude, forest type, location within the mountain range and the presence of the sibling species influenced the occurrence of both treecreepers. Probability of occurrence of the Eurasian Treecreeper increased with altitude except in mountain pine forest, whereas at a given altitude it was lower in Scots pines than in other forest types. In the Short-toed Treecreeper, whose probability of occurrence was enhanced in oak forest, the altitude had a negative influence except in mountain pine forest. In the Eurasian Treecreeper, all other things being equal, probability of occurrence was higher in the forested areas experiencing an oceanic climate than those experiencing a Mediterranean-continental climate. The opposite was found in the Short-toed Treecreeper, whose probability of occurrence on the Pyrenees’ southern slope increased from the western to the eastern end of the mountain range. Finally, the presence of the sibling species decreased the probability of occurrence of both treecreepers at low and medium altitude, suggesting a restricted form of interspecific competition.